Agreement and reliability of lower limb muscle architecture measurements using a portable ultrasound device - Ritsche, Paul; Schmid, Reto; Franchi, Martino V.; Faude, Oliver (Frontiers in Physiology, 2022)
High end ultrasonography devices lack in portability and are expensive. We investigated the agreement and reliability of a handheld and portable ultrasound system for human lower limb muscle architecture measurements. We captured ultrasound images of the rectus femoris (RF), vastus lateralis (VL) and gastrocnemius medialis (GM) in 36 active healthy participants (15 female, 21 male) at 50% of muscle length using the handheld Lumify (L12-4, linear-array 37mm, Philips Healthcare, Amsterdam, Netherlands) and a high-end laboratory device (ACUSON Juniper, linear-array 54mm, 12L3, SIEMENS Healthineers, Erlangen, Germany). We compared measurements of muscle fascicle length, pennation angle and thickness. To assess inter-session reliability of the Lumify system, participants were measured twice within one week. Comparing RF architecture measurements of both devices resulted in intra-class correlations (ICCs) ranging from 0.46-0.82 and standardized mean difference (SMDs) ranging from -0.45-0.05. For VL, ICCs ranged from 0.60-0.89 and SMDs ranged from -0.11-0.13. ICCs and SMDs for the GM ranged from 0.82-0.86 and -0.07-0.07. Calculating inter-session reliability for RF resulted in ICCs ranging from 0.44-0.76 and SMDs ranging from -0.38-0.15. For VL, ICCs and SMDs ranged from 0.57-0.75 and -0.13-0.02. ICCs for GM ranged from 0.75-0.92 and SMDs ranged from -0.15-0.16. Measurement of muscle thickness demonstrated the highest agreement (ICC ≥ 0.82) and reliability (ICC ≥ 0.75) across all muscles. The Lumify system was comparable to a high-end device and reliable for GM measurements. However, agreement and reliability were lower for the RF and VL. Of all evaluated architectural parameters, muscle thickness exhibited highest agreement and reliability.